PEMIKIRAN ZAKIAH DARADJAT TENTANG PEMBINAAN MORAL REMAJA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Radhia Chairunnisa (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2020)
Parents who meet young people often enough (their daughter's son) have an important role to turn their bad morals into good morals. In the field of education, an educator is one of the figures who also participate in changing or improving the morale of the youth around him, and the role of society is also considered influential in improving the morale of youth. This study aims to explain the characteristics of adolescents that must be understood by parents, the problems faced by adolescents themselves, and the factors that influence them, as well as the appropriate methods to foster adolescent morale. This research method uses a type of library research with qualitative data analysis. And data collection method using the works of Zakiah Daradjat as the primary source, and literature, articles, journals, and the internet as the secondary source. The data analysis method is done in three processes, namely data reduction, data presentation, and data verification by comparing the thoughts of other figures with the thoughts of Zakiah Daradjat. The results showed that Zakiah Daradjat's thoughts about adolescence, which at this time were filled with mental shocks and explosive emotions. As well as common problems that occur in the teenager, among others are related to his physical, disputes with parents, competition in school and society, and personal problems that the teenager himself also does not understand what happened to him. Factors that influence the deterioration of youth morale due to lack of religious beliefs as well as lack of supervision and guidance on foreign cultural influences as well as the need for guidance and counseling headquarters. The method that can be done is preventively carried out since the child is in the womb, then repressive which is legal and criminal action but does not corner the teenager, and rehabilitation measures where more consultative agencies are expanded for adolescents who have excessive emotional disorders